PENGARUH TERAPI KOGNITIF PERILAKUAN UNTUK MENURUNKAN GANGGUAN PERILAKU MENENTANG PADA SISWA MTS X DI YOGYAKARTA - Wahyu Kurniawan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
This study aimed to determine the effect of Cognitive Therapy Behavioral to reduce behavioral disorders opposed. Hypothesis proposed in this study is that there is a difference frequency between the opposing behavioral disorders before and after cognitive therapy to students behavioral MTS X in Yogyakarta. Subjects were given cognitive therapy behavioral decreased frequency of behavioral disorders in school against. Subjects in the study of 4 students of class X MTS 8. The design used in this study was a single case study in the form of cognitive therapy behavioral influence. The method of analysis used analysis, visual inspection, interview and observation and analysis of non-parametric (Wilcoxon). The results of hypothesis testing in this therapy is Z for = 0.034 (p> 0.05), Based on the analysis means that there are differences in the frequency of behavioral disorders oppose decrease between before and after cognitive therapy behavioral on MTS X grade 8 students in Yogyakarta.